2005
DOI: 10.1128/jvi.79.5.3206-3210.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Coiled-Coil Domain of the Adenovirus Type 5 Protein IX Is Dispensable for Capsid Incorporation and Thermostability

Abstract: The 14.4-kDa hexon-associated protein IX (pIX) acts as a cement in the capsids of primate adenoviruses and confers a thermostable phenotype. Here we show that deletion of amino acids 100 to 114 of adenovirus type 5 pIX, which eliminates the conserved coiled-coil domain, impairs its capacity to self-associate. However, pIX⌬100-114 is efficiently incorporated into the viral capsid, and the resulting virions are thermostable. Deletion of the central alanine-rich domain, as in pIX⌬60-72, does not impair self-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
4
40
0
1
Order By: Relevance
“…Second, IX has been shown to be associated with purified GONs (1,32). Third, this spatial arrangement agrees with the known stoichiometry of IX and its apparent ability to form multimers (23,34). Lastly, the mass calculated from the difference imaging of the IX trimers was in close agreement with the actual molecular mass of protein IX: 16.6 to 18.9 kDa by scanning transmission electron microscopy versus 14.3 kDa predicted by sequence analysis (12).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Second, IX has been shown to be associated with purified GONs (1,32). Third, this spatial arrangement agrees with the known stoichiometry of IX and its apparent ability to form multimers (23,34). Lastly, the mass calculated from the difference imaging of the IX trimers was in close agreement with the actual molecular mass of protein IX: 16.6 to 18.9 kDa by scanning transmission electron microscopy versus 14.3 kDa predicted by sequence analysis (12).…”
supporting
confidence: 65%
“…Therefore, the volume argument for IIIa assignment also supports the assignment of four protein IX molecules to the same location. Although protein IX has been described as a trimer, the only direct evidence of multimerization has been coimmunoprecipitation data with IX-epitope fusions (23,34), as the protein consistently runs as a monomer on nondenaturing polyacrylamide gels (data not shown). Deletion of the coiled-coil multimerization domain has no effect on the encapsidation of IX or its virion stabilization activity (34).…”
mentioning
confidence: 99%
“…Protein IX is a relatively small capsid protein of 14.4 kDa, but it has gained prominence as a platform for ligand addition for the purposes of vector retargeting and fluorescence labeling (30). Recent studies have shown that only the conserved N-terminal domain of protein IX (amino acids [aa] 1 to 39) is necessary for stabilization of the Ad capsid (34,48). A cryoEM study at 9-Å resolution from our laboratory indicated that the locations identified by STEM for protein IX are likely to correspond to only the N-terminal viral interaction domains (37).…”
mentioning
confidence: 99%
“…During purification, particle-associated pIX molecules were separated from the nonassociated Adenovirus targeting to cancer-testis antigens J de Vrij et al pIX molecules, as nonassociated variants do not copurify with the virus particles in the CsCl gradient. 17,33 A schematic representation of the pIX_TCR A1M1 fusion protein, with its exposed single-chain TCR A1M1 positioned above the hexon capsomers, is depicted in Figure 3a.…”
Section: Efficient Incorporation Of Pix_tcr A1m1 In the Virus Capsidmentioning
confidence: 99%